2017
DOI: 10.1371/journal.pgen.1007095
|View full text |Cite
|
Sign up to set email alerts
|

A MIG-15/JNK-1 MAP kinase cascade opposes RPM-1 signaling in synapse formation and learning

Abstract: The Pam/Highwire/RPM-1 (PHR) proteins are conserved intracellular signaling hubs that regulate synapse formation and axon termination. The C. elegans PHR protein, called RPM-1, acts as a ubiquitin ligase to inhibit the DLK-1 and MLK-1 MAP kinase pathways. We have identified several kinases that are likely to form a new MAP kinase pathway that suppresses synapse formation defects, but not axon termination defects, in the mechanosensory neurons of rpm-1 mutants. This pathway includes: MIG-15 (MAP4K), NSY-1 (MAP3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 67 publications
1
20
0
Order By: Relevance
“…Habituation learning was initially described in the context of reflex responses 1,8 , however there has since been broad recognition that habituation learning is a widespread mechanism associated with and to some degree prerequisite for more complex cognitive processes and behaviors [3][4][5][6]11 . While our understanding of habituation learning both at the molecular and cellular level has been informed predominantly by molecular-genetic studies in invertebrates [18][19][20][21][22][23][24][25][26][27][28] , whether and how additional genetic and circuit mechanisms regulate vertebrate habituation learning has remained largely unclear. Here we describe a previously unappreciated role for the palmitoyltransferase Hip14 in regulating habituation learning, identify the Shaker-like channel subunit Kv1.1 as a Hip14 substrate that also regulates learning, and demonstrate that Hip14 acts to properly target Kv1.1 to presynaptic sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Habituation learning was initially described in the context of reflex responses 1,8 , however there has since been broad recognition that habituation learning is a widespread mechanism associated with and to some degree prerequisite for more complex cognitive processes and behaviors [3][4][5][6]11 . While our understanding of habituation learning both at the molecular and cellular level has been informed predominantly by molecular-genetic studies in invertebrates [18][19][20][21][22][23][24][25][26][27][28] , whether and how additional genetic and circuit mechanisms regulate vertebrate habituation learning has remained largely unclear. Here we describe a previously unappreciated role for the palmitoyltransferase Hip14 in regulating habituation learning, identify the Shaker-like channel subunit Kv1.1 as a Hip14 substrate that also regulates learning, and demonstrate that Hip14 acts to properly target Kv1.1 to presynaptic sites.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on sensory habituation in C. elegans and Aplysia, and startle habituation in zebrafish and rodents have revealed that the synapses between sensory afferents and 'command' interneurons undergo plasticity during habituation [12][13][14][15][16][17] . Furthermore, genetic screens in C. elegans and Drosophila have been instrumental in identifying genes that regulate habituation learning [18][19][20][21][22][23][24][25][26][27][28] . Thus, while a picture of habituation in invertebrates is emerging, a comprehensive view of vertebrate habituation learning is largely absent.…”
Section: Introductionmentioning
confidence: 99%
“…TNIK could activate the JNK kinase pathway ( Taira et al, 2004 ; Fu et al, 1999 ). The MIG-15/JNK-1 signaling pathway inhibits axonal branch formation in s C. elegans ensory neurons ( Crawley et al, 2017 ). In contrast to these well-established roles of MIG-15/TNIK as an activator of the JNK pathway, we did not observe any synaptic tiling defect nor change in synapse number in jnk-1 mutant animals ( Figure 5—figure supplement 2 and data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…This protein family was initially defined as PKM due to Mg 2+ dependent activation, but later renamed, PKC due to Ca 2+ dependent activation [1]. The protein kinase family consists of over 15 subgroups with more than 500 kinases, each of which is involved in the regulation of gene expression; thereby, the downregulation or upregulation of these kinases induces severe consequences in the progression of disorders including neurodegenerative diseases [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%